Multiscreening LC-MS/MS designed for ten pesticide and six antimicrobial residues in eggs - Galvão, Julia Arantes [UNESP]; Yamatogi, Ricardo Seiti [UNESP]; Biondo, Alexanderwelker; Pinto, José Paes de Almeida Nogueira [UNESP]; Silva, José Roberto Marques [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP] (Hindawi, 2017)
A multiscreening method was experimentally validated for pesticide and antimicrobial residues in spiked eggs at levels of 5, 50, and 500 μgL−1. The residue extraction was performed with acetonitrile and 1% formic acid. The extracted material was stored at −70°C until detection and quantitation within 24-hour period by LC-MS/MS. Pesticide and antimicrobial residue recovery performed adequate standard deviation and the results were from 94.10% (ampa) to 9.20% (carbaryl) for pesticides and from 95.70% (enrofloxacin) to 46.20% (sulfathiazole) for antimicrobial.Themethod was highly accurate, considering the linearity for all pesticide and antimicrobial residues (r2> 0.99), with quantitation limits ranging from 0.78 to 6.25 μgL−1 for pesticides and 0.78 to 3.13 μgL− 1 for antibiotics. A highly correlation coefficient (r > 0.99) was found, except for carbaryl. Although time extraction and carbaryl recovery remain to be improved, the method has shown a rapid pesticide and antimicrobial residue detection.